Carbon Sphere‐Polyaniline Composite: A Fluorescent Scaffold for Proliferation of Adipose Derived Stem Cells and its Cellular uptake. Issue 12 (3rd August 2016) - Gandla , Dayakar; Putta, Chandrababu; Ghosh , Sutapa; Hazra, Binoy Krishna
Abstract: In this work, for the first time, we used inherently fluorescent carbon spheres (IF‐CSP) as a doping agent to retain the electroactivity of polyaniline (PANI) in neutral media by making composite (IF‐CSP@PANI) which is an important requirement for physiological applications of PANI. To address this issue, in situ chemical oxidative polymerization of aniline is done in presence of IF‐CSP. IF‐CSP@PANI has higher electrochemical activity than PANI in cell culture media at pH 7.4 with high cycling stability which was confirmed by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). In addition, this material showed great promise as a biocompatible scaffold for the adherence and proliferation of adipose derived stem cells (ADSCs) at all concentrations of IF‐CSP@PANI composite (10‐200 μg/mL) for five days of culture period and this was confirmed by MTT assay. Doping of PANI with IF‐CSP might have helped to preserve its electroactivity and cycling stability at higher pH values by hindering the deprotonation of its conducting form. Proliferation of ADSCs may be attributed to the electroactivity of the composite material. Confocal laser scanning microscopy (CLSM) images evidenced that the IF‐CSP@PANI composite was able to enter into the cytoplasm of ADSCs. These extraordinary properties might render the IF‐CSP@PANI composite as a promising candidate for bioimaging, biosensing, tissue engineering and drug or gene delivery. Abstract : The enhanced property: The polyaniline coated inherently fluorescent carbon spheres composite is synthesized by in situ chemical oxidative polymerization which is showed great promise as a biocompatible scaffold for the adherence and proliferation of adipose derived stem cells and also localized in their cytoplasm.